Improving Vocabulary Mastery Using Folktales At The Sixth Year Of SD Negeri 3 Jatingarang Weru Sukoharjo: An ActionResearch - Sari, Inggrit Priana, Drs. Djoko Srijono. M.Hum, Aryati Prasetyarini. M.Pd (2013)
The process of improving vocabulary using folktale technique was conducted by using clasroom action research (CAR). It involed four steeps such as planning, acting/implementing, observing, and reflecting. This research was implemented into two cycles consisted of three meeetings. The improving vocabulary mastery using folktale was succesfully. It started from before the cycle, the writer did pre-test to know the ability the students vocabulary mastery. In cycle I after implementing vocabulary mastery using folktale the students still have low score and theaching-learning process still crowded and there is some students did not answer teacher's question because they stand by their selves. In cycle II the teaching-learning process more effective because they are in a group, so they help eeeach otehr to answer the teacher's question. The result of improving students' vocabulary mastery for sixth year students of SDN 3 Jatingarang was great. The improvement of the students' vocabulary mastery can be seen from the significant improvement of the students' score in each cycle. The result of the pre-test score is 49,9 (before treatment) and the average of the post-test I scoore is 92,00 (after being the treatment in cycle I). While after the treatment in cycle II, the average of the students' score shows a great improvement that is 93,6.